Reinventing the organization for GenAI and LLMs - Mollick, Ethan 1975- (MIT Sloan Management Review, 2024)
Previous technology breakthroughs did not upend organizational structure, but generative AI and LLMs will. We now face a challenge like that of the original railroad operators: how to rebuild an organization around a fundamental shift in the way work is done, organized, and communicated. What is your organization's vision about how AI makes work better, not worse? Managers must start answering that question. To guide your thinking, use these three principles for reorganizing work around AI.
Reprint #65411
Keywords: Artificial intelligence; Natural language processing (Computer science); Business -- Data processing; Business -- Technological innovations; Intelligence artificielle; Traitement automatique des langues naturelles; Gestion; Informatique; Affaires; Innovations; artificial intelligence